2017
DOI: 10.1111/cea.12900
|View full text |Cite
|
Sign up to set email alerts
|

H1‐antihistamine‐refractory chronic spontaneous urticaria: it's worse than we thought – first results of the multicenter real‐life AWARE study

Abstract: This study reveals that German H1-antihistamine-refractory CSU patients have high rates of uncontrolled disease, angioedema, and comorbid CIndU, are undertreated, have impaired QoL, and rely heavily on healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
4
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 39 publications
12
104
4
14
Order By: Relevance
“…The use of patient‐reported outcome measures such as the urticaria activity score (UAS), the angioedema activity score (AAS), the CU quality of life questionnaire (CU‐Q2oL), the angioedema quality of life questionnaire (AE‐QoL) and the urticaria control test (UCT) in studies and clinical practice has helped to better define the effects and impact of CU on patients . The available data indicate that urticaria markedly affects both objective functioning and subjective well‐being . Previously, O'Donnell et al showed that health status scores in CSU patients are comparable to those reported by patients with coronary artery disease .…”
Section: Definitionmentioning
confidence: 99%
“…The use of patient‐reported outcome measures such as the urticaria activity score (UAS), the angioedema activity score (AAS), the CU quality of life questionnaire (CU‐Q2oL), the angioedema quality of life questionnaire (AE‐QoL) and the urticaria control test (UCT) in studies and clinical practice has helped to better define the effects and impact of CU on patients . The available data indicate that urticaria markedly affects both objective functioning and subjective well‐being . Previously, O'Donnell et al showed that health status scores in CSU patients are comparable to those reported by patients with coronary artery disease .…”
Section: Definitionmentioning
confidence: 99%
“…Angioedema is defined as rapid swelling at a deeper level under the skin than hives, occurring on the face, inside the mouth or elsewhere on the body . It is estimated that 33%‐67% of patients with CSU exhibit both hives and angioedema, 29%‐65% exhibit only hives and 1%‐13% exhibit only angioedema …”
Section: Introductionmentioning
confidence: 99%
“…Patients with CSU‐associated angioedema often experience concern over their health status, at times worrying that swelling episodes may cause problems with breathing or may be life‐threatening . A real‐world multicentre study in Germany has shown that in a 6‐month period, more than 40% of patients with inadequately controlled CSU experienced angioedema; among these patients, 78% rated their angioedema as severe or moderate in intensity, and a mean of 34 days with angioedema was reported during the 6‐month period . In addition to its considerable symptom burden, recurrent angioedema (in those with hereditary angioedema) can lead to absenteeism and can have a negative impact on work productivity …”
Section: Introductionmentioning
confidence: 99%
“…1 However, many patients with CSU do not show complete control of their disease with standard doses. 97 In these patients, updosing of up to fourfold higher than standard doses of their H 1 antihistamine is recommended by the current EAACI/GA 2 LEN/ EDF/WAO guideline for urticaria. 1 Several studies have confirmed that treatment of CSU by higher than standard doses of H 1 antihistamine, that is updosing of an sgAH, is more effective than treatment with the standard dose for most sgAHs.…”
Section: Con Clus Ionsmentioning
confidence: 99%